Pengaruh Kegiatan 3 M Terhadap Kemampuan mototik Halus Anak Di Kelompok B TK Alkhairaat Layana Indah - Amelia rahma Dani Suriyani; Fitriana; Amrullah; Andi Agusniatih (Jurnal Pelita PAUD, 2025)
Abstract: The problem in this research lies in the child's fine motor skills. This research aims to determine the effect of 3 M activities on children's fine motor skills. The research method used in this research is quantitative and the type of research used is experimental. Data collection techniques through observation, interviews and documentation. Data management is carried out using a percentage formula. Based on the results of observations before and after treatment, the child's independence aspect for the BSB category from 0% to 40%, BSH category from 13.33% to 53.33%, MB category from 46.66% to 6.66%, BB category from 40% to 0%. Meanwhile, the second aspect of children's creativity for the BSB category from 0% to 40%, BSH category from 13.33% to 53.33%, MB category from 40% to 6.66%, BB category from 46.66% to 0%. Meanwhile, the third aspect of children's communication for the BSB category from 0% to 33.33%, for the BSH category from 13.33% to 40%, for the MB category 20% from 26.66%, and for the BB category from 66.66% to 0%. Apart from that, the calculated t value is 5.351> ttable 1.76131, so it can be concluded that Ho is rejected and HÄ± is accepted, meaning that there is an influence of 3M activities on the fine motor skills of children in Group B of Alkhaairat Layana Indah.